Komunikasi Dakwah Dan Peran Ulama Dalam Mencegah Pernikahan Dini Di Nusa Tenggara Barat - Lalu Ahmad Zaenuri; Andri Kurniawan (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2021)
This study aims to determine the involvement, role and da’wah communication of ulama in preventing early-age marriage in West Nusa Tenggara. This study uses a qualitative approach and library research. Data collection techniques using the literature review through various references related to research. The results of the research through a literature review are looking at government programs such as those related to early-age marriage, then the stakeholders involved are not enough from government agencies only. It’s also important the involvement and role of ulama as role models for the community in suppressing cases of early-age marriage through da'wah communication activities and forming special guidance and assistance programs for parents and adolescents regarding the negative impacts on early-age marriage.